Do bico à boca: o trabalho itinerante no cultivo de uva em São Miguel Arcanjo, SP - Manente, Ingrid Yasmine (Universidade Federal de São Carlos, 2021)
The present monograph deals with the working conditions of the well-known grape workers of the city of São Miguel Arcanjo, a small town in the southwest of São Paulo. The production of grapes in the city is known in the state of São Paulo, and all the São Miguel cultural tradition revolves around the grape, for being one of the main agricultural products produced by the city. In this work, we gave voice to the workers, so that they could report their working conditions, income, and the reasons for becoming cold boiled in the cultivation and thinning of grapes in the city.
From beak to mouth: the itinerant work in grape cultivation in São Miguel Arcanjo, SP
Keywords: condições de trabalho; trabalho na uva; produção de uva; São Miguel Arcanjo; boias-frias; CIENCIAS HUMANAS::SOCIOLOGIA::SOCIOLOGIA RURAL